Ion specific effects of alkali cations on the catalytic activity of HIV-1 protease - Pokorná, Jana; Heyda, Jan; Konvalinka, Jan (Faraday discussions, 2013)
Human immunodeficiency virus 1 protease (HIV-1 PR), an important therapeutic target for the treatment of AIDS, is one of the most well-studied enzymes. However, there is still much to learn about the regulation of the activity and inhibition of this key viral enzyme. Specifically, the mechanism of activation of HIV-1 PR from the viral polyprotein upon HIV maturation is still not understood. It has been suggested that external factors like pH or salt concentration might contribute to regulation of this crucial step in the viral life cycle. Recently, we analyzed the activity of HIV-1 PR in aqueous solutions of sodium and potassium chloride by experimental determination of enzyme kinetics and molecular dynamics simulations. We showed that the effect of salt concentration is cation-specific [Heyda et al., Phys. Chem. Chem. Phys., 2009 (11), 7599]. In this study, we extended this analysis for other alkali cations and found that the dependence of the initial velocity of peptide substrate hydrolysis on the nature of the cation follows the Hofmeister series, with the exception of caesium. Significantly higher catalytic efficiencies both in terms of substrate binding (K(M)) and turnover number (kcat) are observed in the presence of K+ compared to Na+ or Li+ at corresponding salt concentrations. Molecular dynamics simulations suggest that both lithium and sodium are attracted more strongly than potassium and caesium to the protein surface, mostly due to stronger interactions with carboxylate side chain groups of aspartates and glutamates. Furthermore, we observed a surprising decrease in the K(M) value for a specific substrate at very low salt concentration. The molecular mechanism of this phenomenon will be further analyzed.
Keywords: simulace molekulární dynamiky; HIV-proteasa; Alkalies; kationty; alkálie; Hydrogen-Ion Concentration; Cations; Molecular Dynamics Simulation; biokatalýza; Biocatalysis; HIV Protease; koncentrace vodíkových iontů